An analysis of policy and funding priorities of global actors regarding noncommunicable disease in low- and middle-income countries - Kanykey Jailobaeva; Jennifer Falconer; Giulia Loffreda; Stella Arakelyan; Sophie Witter; Alastair Ager (BMC, 2021)
Abstract Background Noncommunicable diseases (NCDs), including mental health, have become a major concern in low- and middle-income countries. Despite increased attention to them over the past decade, progress toward addressing NCDs has been slow. A lack of bold policy commitments has been suggested as one of the contributors to limited progress in NCD prevention and management. However, the policies of key global actors (bilateral, multilateral, and not-for-profit organisations) have been understudied. Methods This study aimed to map the key global actors investing in action regarding NCDs and review their policies to examine the articulation of priorities regarding NCDs. Narrative synthesis of 70 documents and 31 policy papers was completed, and related to data collated from the Global Health Data Visualisation Tool. Results In 2019 41% of development assistance for health committed to NCDs came from private philanthropies, while that for other global health priorities from this source was just 20%. Through a range of channels, bilateral donors were the other major source of NCD funding (contributing 41% of NCD funding). The UK and the US were the largest bilateral investors in NCDs, each contributing 8%. However, NCDs are still under-prioritised within bilateral portfolios - receiving just 0.48% of US funding and 1.66% of the UK. NGOs were the key channels of funding for NCDs, spending 48% of the funds from donors in 2019. The reviewed literature generally focused on NCD policies of WHO, with policies of multilateral and bilateral donors given limited attention. The analysis of policies indicated a limited prioritisation of NCDs in policy documents. NCDs are framed in the policies as a barrier to economic growth, poverty reduction, and health system sustainability. Bilateral donors prioritise prevention, while multilateral actors offer policy options for NCD prevention and care. Even where stated as a priority, however, funding allocations are not aligned. Conclusion The growing threat of NCDs and their drivers are increasingly recognised. However, global actors' policy priorities and funding allocations need to align better to address these NCD threats. Given the level of their investment and engagement, more research is needed into the role of private philanthropies and NGOs in this area.